Poverty and Intrahousehold Gender Inequality in Time Use in Ghana. Issue 4 (2nd October 2022) - Orkoh, Emmanuel; Claassen, Carike; Blaauw, Derick
ABSTRACT: How gender-based differences in time spent on household and labor-market activities affect men's and women's well-being is of growing interest to economists and policymakers. In many countries, women perform more unpaid work than men and have fewer opportunities to lift themselves out of poverty through education and training. This article analyzes the relationship between poverty and gender inequality in time use among monogamous couples in Ghana. A key finding is that women in poor households face heterogeneous levels of inequality in time use, depending on the type of activity, inequality in time use, and characteristics of the household. The study highlights the importance of devising gender-aware policies and altering entrenched cultural stereotypes, thereby helping to reduce inequality between men and women. This should afford more women the opportunity to play a more productive and economically meaningful role in the formal labor market. HIGHLIGHTS In Ghana, poor households face significantly higher gender inequality in time use compared to rich households. Levels of time-use inequality for poor women vary in relation to activity and household characteristics. Policies should prioritize reducing poverty to alleviate intrahousehold inequality. Gender-aware policies should address norms that impede women's labor market participation and autonomous time allocation.